Legal Studies on EU Policies: Why Labour Migration Status as a Binary - Nguyen Thuy Anh (Fiat Justisia: Jurnal Ilmu Hukum, 2023)
In the framework of the post-Covid-19 pandemic, Europe is facing two problems in terms of migrant workers: a shortage of agricultural production workers in some countries and the "coercive acceptance" of undocumented migrant workers. Most EU countries are in a state of economic recovery after the pandemic, so production activities need to be restored at a reasonable cost. However, the aging population in some European countries is forcing governments to hire foreign workers at high costs. To balance the needs in the economic calculation, irregular migrant workers are considered a suitable temporary solution. Besides, reopening diplomatic programs with strategic partner countries is extremely urgent. Therefore, the question of reducing illegal migration without building an iron wall in diplomacy is remarkable. In this context, the author based on the analysis of EU policy for migrant workers and based on the case of Spain and the methodology applied to answer research questions will be based on comparison qualitative research. I focus on analyzing the concept between illegal and irregular migration from the perspective of human rights law and humanitarian factors. In addition, there are aspects of migrant workers in some EU legal documents to protect the rights of migrant workers and their families.